PENCAPAIAN KETUNTASAN HASIL BELAJAR DENGAN MODEL SNOWBALLING PENDEKATAN CONTEXTUAL TEACHING AND LEARNING - Putranto, Tutut Adi; Susatyo, Eko Budi; Siadi, Kusoro (Chemistry in Education, 2013)
This research used a model of learning Snowballing trough CTL to present the material. This research was done to know students of Grade XI SMA Negeri Banyumas learning completeness of Buffer and Hydrolysis material by using Snowballing trough CTL methodology . The design was  post-test only control group design. The sample was taken by using random cluster technique, namely two random class, experiment and control class. It was found in a range that learning result  average score at experiment class was  = 83,31 and  control class was = 77,06. Based on  learning completeness trial, experiment class obtained  tcalculate = 6,39 with t(1-α)(n-1) = 2,04, so experiment class reached learning completeness. While control class got  tcalculate = 1,99 with t(1-α)(n-1) = 2,03, meant it did not fulfill learning completeness. It was concluded that teaching and learning activity by using snowballing methodology through CTL can fulfill learning completeness of SMA students of Buffer and Hydrolysis material.